LRRK2 and membrane trafficking: nexus of Parkinson's disease - Hur, Eun-Mi; Jang, Eun-Hae; Jeong, Ga Ram; Lee, Byoung Dae (BMB reports, 2019)
Recent evidence from genetics, animal model systems and biochemical studies suggests that defects in membrane trafficking play an important part in the pathophysiology of Parkinson's disease (PD). Mutations in leucine-rich repeat kinase 2 (LRRK2) constitute the most frequent genetic cause of both familial and sporadic PD, and LRRK2 has been suggested as a druggable target for PD. Although the precise physiological function of LRRK2 remains largely unknown, mounting evidence suggests that LRRK2 controls membrane trafficking by interacting with key regulators of the endosomal-lysosomal pathway and synaptic recycling. In this review, we discuss the genetic, biochemical and functional links between LRRK2 and membrane trafficking. Understanding the mechanism by which LRRK2 influences such processes may contribute to the development of disease-modifying therapies for PD. [BMB Reports 2019; 52(9): 533-539].